Factors Influencing Conative Loyalty in Anthropology Museum Tourism - Jing Jing Zheng; Hua wen Shen; Ka Yin Chau; Ting Liu; En Long Li (Tourism & Management Studies)
Although the concepts of loyalty, service quality and customer satisfaction have frequently been discussed by scholars, their connections with emotional factors have rarely been investigated in the field of museum tourism. The Anthropology Museum of Guangxi focuses on unique ethnic minorities, which is used as a case study in this paper. The key question is whether visitors are driven by certain emotional factors. This paper examines the relationships among the factors that influence visitors’ emotional attachment, satisfaction, conative loyalty and perceived quality. Structural equation modelling (PLS-SEM) is used to model the relations among these four constructs, which include formative and reflective constructs. The structural model was tested on a sample of 184 visitors to the Anthropology Museum of Guangxi, and empirical study of the conceptual model supports all of the paper’s hypotheses. The results show positive influences among emotional attachment, visitor satisfaction and perceived quality, which may indeed affect visitors’ conative loyalty to a specific museum. The practical applications are suggested based on the finding that emotional attachment plays an important role in predicting visitor loyalty.